2020
DOI: 10.1177/2050640619887580
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, randomized comparison of the diagnostic accuracy of 19‐gauge stainless steel and nitinol‐based needles for endoscopic ultrasound‐guided fine‐needle biopsy of solid pancreatic masses

Abstract: Background The use of 19-gauge (G) stainless steel needles for endoscopic ultrasound-guided fine-needle biopsy of a pancreatic mass often results in technical difficulties due to an inability to advance the relatively rigid needle out of the endoscope. More flexible nitinol-based needles might decrease such technical difficulties and thus increase diagnostic accuracy. Objective In this prospective multicenter randomized single-blinded study we compared the diagnostic value of those two needle types in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a randomized trial on 46 patients, two 19G needles were employed: a nitinol‐based and a stainless steel one. The diagnostic accuracy was similar for both needles, with a slight reduction in time spent for puncturing for nitinol‐based needle 8 …”
Section: Endoscopymentioning
confidence: 84%
See 2 more Smart Citations
“…In a randomized trial on 46 patients, two 19G needles were employed: a nitinol‐based and a stainless steel one. The diagnostic accuracy was similar for both needles, with a slight reduction in time spent for puncturing for nitinol‐based needle 8 …”
Section: Endoscopymentioning
confidence: 84%
“…The diagnostic accuracy was similar for both needles, with a slight reduction in time spent for puncturing for nitinol-based needle. 8 © 2021 The Authors. UEG Journal published by Wiley Periodicals LLC.…”
Section: Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Benchtop tests conducted by Itoi et al proved that, in contrast to traditional 19G needles, 19G nitinol needles can be inserted at the optimal angle with minimal resistance under various endoscope bending conditions [ 41 ]. A multicenter, prospective, randomized, double-blind study of EUS-FNB needles applied to solid pancreatic masses by Hann et al showed no significant difference in diagnostic rates between 19G stainless-steel needles (65.9%) and 19G nitinol needles (68.3%) ( p = 0.73) [ 42 ]. However, nitinol needles reduce the puncture time and technical failure rate (i.e., the needle cannot be bent or inserted twice).…”
Section: Development Of Puncture Needlesmentioning
confidence: 99%